O ensino de arte pós-moderno na arte de Daniel Francisco de Souza - Sá, Raquel Mello Salimeno de (2016)
This thesis presents a research that links cultural history and visual culture in a sociobiographical approach. It gives a “political treatment” to the educational experience in the transition of art teaching from the modern to the postmodern. By taking into account my experiences as an educator and the poetic practice in Daniel Francisco de Souza’s visual art, I propose a dialogue with his art and a series of visual narratives this artist/student produced at the time of his education and recently. Such visual narratives were taken as research source and research subject. They were created in a rural setting in dialogue with formal art teaching in two phases: 1992–6, when Daniel Fran cisco attended elementary school in the rural area of Uberlândia, MG; and 2008–10, when he attended Visual Arts graduation at Federal University of Uberlândia city. I analyze historical processes related to art and teaching, from the early sixteenth century to the present times, to realize residues in students’ poetic experiences. I relate Brazilian educational public policies with experi- ences in that rural school. I try to show the extent to which our educational practices triggered experiences — from ones common to intense ones — and promoted forms of “emancipation-knowledge” or “regulation-knowledge” and how the “selective tradition” was and how art predetermined history images gave way to everyday visual references, pointing to the “broad field” of visual culture. I make an effort to show Daniel Francisco’s work as an adult by tak- ing it according to different approaches. In a poetic reading, first, I emphasixe the material and the symbolic in his art. In a second look, I approach his work through the intertwining experiences of three characters from different times and places that participated in the making of his art: the artist farmer, the artist teacher and the teacher researcher. I assume the existence of a mutual cultural incompleteness in these three characters; which means that parts of their “structures of feeling” built on the interrelationship among them are part of the artist’ work as a historical content decanted. Thirdly, I demonstrate how the artist sees his place as a key re ference to his poetic creation. His work does not reflect the rural bucolic as something untouched. In showing the difficulty in distinguishing the archaic residual, I identify emerging issues in his work. I conclude that the artist — Daniel Francisco — and the researcher — myself — present maverick features: both are scavengers; their productions approach the working with scraps in art and in the academy; even momentarily, they live in exile in the warmth of the borders or the edges, from where one sees the center clearly. In these spaces, when certain structures and normative codes enter into coalition, they fragment pre-established strategies and stimulate the creation of survival tactics.